Influence of the shape of the impactor on residual strength, size and nature of damage to CFRP - Przybyłek, Paweł; Komorek, Andrzej; Kaczor Di Paola, Simone Taddeo; Komorek , Łukasz (Technologia i Automatyzacja Montażu (Assembly Techniques and Technologies), 2022)
The experimental tests presented in this work concern the impact resistance test and residual strength properties after an impact performed by a drop tower INSTRON CEAST 9340. The authors prepared samples of a composite material with a polymeric matrix L285 and H285 hardener, reinforced with eight ply fabric of carbon fibre. Two shapes of the impactor (spherical and V-shape) were used to perform the testing. The samples were impacted by three values of energy (10, 15, 20 [J]). Three-point bending tests were performed to the residual strength of the samples subjected to impact tests and compared to samples which had not been damaged earlier. The study showed differences in the influence of the shapes of the impactor on the nature of the composite damage. After the test, conclusions were drawn about the influence of the shape of the impactor on the area of composite damage and its character. Also, its influence on residual strength was described. Despite the clear differences in the area of damage to composites impacted by different impactors, this does not have a significant influence on the residual strength. This is an Open Access article distributed under the terms of the Creative Commons Attribution License CC BY 4.0 (https://creativecommons.org/licenses/by/4.0/)